Landslides in Urquiza Park: The Use of PET Fibers to Avoid the Movement of Hillsides - Londero, Bautista; Lopez, David José (My University, 2023)
Summary—Urquiza Park is an important green area of the city of Paraná. Currently, it is facing a critical issue related to landslides and erosion. The causes are mainly heavy rains and trees removal, destroying the environment and putting people at risk. The purpose of this project is to address the issue of landslides within the specific area of Urquiza Park. To fulfill this aim, a solution that can be implemented by future civil engineers will be explored and explained, involving the reuse of recycled PET fibers to prevent landslides and erosion of this area. In order to achieve the goal of this work, it is organized as follows. Firstly, the city of Paraná will be briefly described. Then, the Urquiza Park landslides problem will be presented and discussed. Next, some scenes will be described in order to help visualize the problematic situation. Later, the causes as well as the consequences of the problem will be identified and analysed. After this, the solution to address the problem will be discussed. Finally, the strengths and weaknesses of the proposal will be stated. The expected impact of this project is mainly to improve the quality of life and safety of people as well as to preserve an important landmark of Paraná like Urquiza Park. In addition, it contributes to raising social awareness regarding PET recycling.

Resumen— El Parque Urquiza es una importante zona verde de la ciudad de Paraná. Actualmente, enfrenta un problema crítico relacionado con deslizamientos de tierra y erosión. Las causas son principalmente las fuertes lluvias y la tala de árboles, que destruyen el medio ambiente y ponen en riesgo a las personas. El propósito de este proyecto es abordar el problema de deslizamientos de tierra en el área específica del Parque Urquiza. Para cumplir con este objetivo, se explorará y explicará una solución para que la puedan implementar los futuros ingenieros civiles, que consiste en la reutilización de fibras de PET recicladas para evitar deslizamientos y erosión de esta zona. Para lograr el objetivo de este trabajo, se organiza de la siguiente manera. En primer lugar, se describirá brevemente la ciudad de Paraná. Luego, se presentará y discutirá el problema de los deslizamientos de tierra en el Parque Urquiza. A continuación, se describirán algunas escenas para ayudar a visualizar la situación problemática. Posteriormente se identificarán y analizarán las causas y las consecuencias del problema. Después de esto, se discutirá la solución para abordar el problema. Finalmente se expondrán las fortalezas y debilidades de la propuesta. El impacto esperado de este proyecto es principalmente mejorar la calidad de vida y seguridad de las personas, así como preservar un punto de referencia importante de Paraná como lo es el Parque Urquiza. Además, se contribuye a generar conciencia social respecto al reciclaje de PET.
Keywords: Inglés I, geotextiles, landslides and erosion, recycled PET fibers, social awareness.; Inglés I,geotextiles, deslizamientos y erosión, fibras PET recicladas, conciencia social.